Features of some growth factors content in tumors and blood plasma in patients with rare forms of endometrial cancer - E. M. Frantsiyants; V. A. Bandovkina; T. I. Moiseenko; A. P. Menshenina; M. A. Rogozin; I. V. Kaplieva; E. I. Surikova; I. V. Neskubina; Yu. A. Petrova; N. D. Cheryarina; M. L. Adamyan; O. E. Zhenilo; et al. (Исследования и практика в медицине, 2025)
Purpose of the study. The objective of the present study was to examine the levels of TGFβ1, EGF, and EGFR in the blood and tissue of morphologically distinct endometrial tumors, including uterine serous carcinoma (USC), clear cell endometrial cancer (CCEC), and G3 endometrioid adenocarcinoma (EAC).Patients and methods. The study encompassed 61 patients diagnosed with uterine body cancer, including 21 patients with USC, 20 patients with CCEC, and 20 patients with EAC (G3). All patients underwent a thorough morphological verification of the disease, as documented in the postoperative report. The level of epidermal growth factor and its receptor (EGF and EGFR), as well as transforming growth factor (TGFb1), was determined in cytosolic fractions of 10 % tumor homogenates and blood samples using standard ELISA kits. Samples of intact endometrium obtained from patients who underwent surgery for uterine fibroids (n = 20) and blood samples from conditionally healthy women (n = 20) of the same age served as normal indicators. Statistical analysis of the results was performed using the Statistica 10.0 software package.Results. EAC (G3) was characterized by an increased, compared to the healthy, content of growth factors and their receptors in tumor and blood samples. In tumor samples of CCEC and USC, the level of TGFβ1 was lower by 2.2 times and 1.6 times, respectively, and the concentration of EGF was on average more than 2 times lower, compared to the indicators in the intact endometrium. The content of these same growth factors in blood samples in patients with rare forms of EC exceeded the normative values by 2.1–4.2 times.Conclusion. The investigation revealed that low levels of EGF were present in tumor samples of rare forms of endometrial cancer, accompanied by unaltered levels of EGFR and TGFβ1. This observation stands in contrast to the elevated concentrations of these growth factors detected in blood samples. The distinctive profile of these growth factors in tumor samples differentiates them from the indicators observed in EAC tissue, where the levels of EGFR and TGFβ1 are augmented. It is plausible that the altered metabolism of non-endometrioid uterine cancers leads to alterations in the biological characteristics of tumors, consequently resulting in a more aggressive clinical course.